INVESTIGATING JUNIOR HIGH SCHOOL STUDENTS’ ERRORS IN USING ENGLISH PAST TENSE: A LOOK FROM TECHNOLOGICAL AND SOCIOLOGICAL FOUNDATIONS - Putu Pande Novita Sari; Made Hery Santosa; Ni Luh Putu Sri Adnyani (Universitas Islam Negeri Alauddin Makassar, 2020)
This study aims at investigating junior high school students’ errors in using English past tense in their English compositions. The subjects of this study were 8th-grade students in a junior high school in North Bali. This study employed descriptive qualitative research which describes the error that was produced by EFL learners. There were four steps in collecting the data namely, asking the students to watch a video, telling them to write recount text through guided writing, collecting the learners' writing, identifying the students' errors in writing past tense, and classifying the errors. The data were analysed using Corder's framework to classify students' errors. The study revealed that there were nine types of errors produces by EFL learners. The errors are applying Indonesian syntactic pattern, using Indonesian acronym, omitting the plural marker -s, adding plural marker -s in a singular form, deleting BE, using incorrect word choice, adding articles, overgeneralising, and using incorrect word order. The errors show that the students tend to use their native language structure in composing the English past tense. Hence, the errors made by students and acknowledged by teachers should be addressed immediately by implementing appropriate strategies and materials to enhance learning. Furthermore, this study can be conducted for further research with different subjects as well as references for applied linguistics courses.